Genotoxicity study of dimethyl isophthalate in bacterial and mammalian cell system - Chung, Young-Shin; Choi, Seon a; Hong, Eun-Kyung; Ryu, Jae-Chun; Lee, Eunjung; Choi, Kyunghee (KOREAN SOCIETY TOXICOGENOMICS & TOXICOPROTEOMICS-KSTT, 2007)
This study was conducted to evaluate the mutagenic potential of dimethyl isophthalate (DMIP) using Ames bacterial reverse mutation test, chromosomal aberration test and mouse lymphoma tk(+/-) gene assay. As results, in Ames bacterial reversion assay, DMIP was tested up to the concentration of 5,000 mu g/plate and did not induce mutagenicity in Salmonella typhimurium strains TA98, TA100, TA1535 and TA1 537, and Escherichia coli WP2uvrA with or without metabolic activation (S9 mix). Using cytotoxicity test, the maximal doses of DMIP for chromosomal aberration assay were determined at 1,250 mu g/mL, which was a minimum precipitation concentration (IC50 > 1,940 mu g/mL or 10 mu M) and at 155 mu g/mL (IC50: 155 mu g/mL) in the presence and the absence, respectively, of S9 mix. DMIP in the presence of S9 mix induced statistically significant (P<0.001) increases in the number of cells with chromosome aberrations at the dose levels of over 250 mu g/mL, when compared with the negative control. However, DMIP in the absence of S9 mix did not caused significant induction in chromosomal aberrant cells. In MLA, DMIP at the dose range of 242.5-1,940 mu g/mL in the presence of S9 mix induced statistically significant increases in mutation frequencies related to small colony growth, whereas any significant mutation frequency was not observed in absence of S9 mix. From these results, it is conclusively suggested that dimethyl isophthalate may be a clastogen rather than a point mutagen.
Keywords: MOUSE LYMPHOMA-CELLS; RESISTANT TFT MUTANTS; MUTAGENICITY TEST; TRANSFORMATION; TEREPHTHALATE; CARCINOGENS; TOXICITY; ASSAY; MODEL